Oral manifestations of diabetes mellitus in complete denture wearers - de Lima, Danielle Cristina [UNESP]; Nakata, Gislaine Cristina [UNESP]; Balducci, Ivan [UNESP]; Almeida, Janete Dias [UNESP] (Mosby-elsevier, 2008)
Statement of problem. The oral mucosa has been reported to show a variety of changes in subjects with diabetes mellitus.Purpose. The purpose of this study was to compare diabetic and nondiabetic subjects wearing complete dentures with regard to salivary flow, salivary buffering capacity, denture retention, and oral mucosal lesions.Material and methods. Sixty subjects, 30 with and 30 without a diagnosis of diabetes, were matched for gender, race, and age. Salivary flow, salivary buffering capacity, glycemia, blood pressure, presence of mucosal lesions, denture retention, use of medications, and behavioral factors (controlled or uncontrolled diet, alcohol consumption, and smoking) reported by the subjects, were evaluated. For the salivary buffering capacity test, 1 mL of saliva was pipetted into a test tube containing 3 mL 0.005 N of hydrochloric acid, and the pH was measured with indicator strips. Group differences were statistically analyzed using the Student t test and the Mann-Whitney test for quantitative variables and the chi-square test for qualitative variables (alpha = .05).Results. Mean (SD) salivary flow was 1.14 (0.87) mL/min in the nondiabetic subjects and 0.95 (0.61) mL/min in the diabetic subjects. Evaluation of self-reported denture retention revealed no significant difference between groups. Denture retention was observed in 66.7% (20/30) of the control group and in 50% (15/30) of the diabetic group. The prevalence of mucosal lesions was 90% (27/30) in the control group and 83.3% (25/30) in the diabetic group. Salivary buffering capacity was 5.80 (0.85) in the control group and 5.26 (0.83) in the diabetic group (P = .017).Conclusions. Within the limitations of this study, no significant differences were observed in salivary flow, denture retention, or oral lesions in diabetic and nondiabetic subjects.